Laminate, method for manufacturing laminate, and method for manufacturing connection structure
By designing a laminated body structure with a specific adhesion strength ratio in the circuit connection and the hot pressing method, the problems of deterioration of the adhesive film and the peeling of the substrate are solved, and a more stable circuit connection is achieved.
Patent Information
- Application Number
- CN202380037610.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-02
- Filing Date
- 2023-04-24
- Publication Date
- 2025-01-03
AI Technical Summary
The existing circuit connection adhesive film deteriorates during drying, deteriorates adhesion, is easy to peel off during handling and cutting, and the substrate is easy to peel off during use, resulting in adverse conditions.
A laminated structure is designed in which the adhesion strength ratio of the first substrate and the second substrate is in the range of 0.25 to 0.80. By placing a conductive adhesive film between the first substrate and the second substrate, the The hot pressing method realizes electrical connection of circuit components to ensure the stability and connection strength of the adhesive film.
The drying deterioration of the adhesive film is effectively suppressed, the peeling of the substrate is reduced, and the stability and connection strength of the laminated body are improved during handling and use.
Smart Images

Figure CN119256058A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate, a method for producing a laminate, and a method for producing a connected structure. Background Art
[0002] In the past, for example, an adhesive film was used to heat and pressurize opposing circuit components and electrically connect electrodes in the pressurized direction. As such an adhesive film for circuit connection, for example, an adhesive film for circuit connection in which conductive particles are dispersed in an adhesive is known (for example, refer to the following patent documents 1 to 4).
[0003] Recently, even when semiconductor chips such as driver ICs are directly mounted face-down on LCD panels or printed circuit boards, a so-called chip-on-glass (COG) mounting method in which semiconductor chips are directly mounted on substrates has been adopted instead of the conventional wire bonding method. Here, too, a circuit connection adhesive film is used as a circuit connection material.
[0004] Previous technical literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 60-191228
[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 1-251787
[0008] Patent Document 3: Japanese Patent Application Laid-Open No. 7-90237
[0009] Patent Document 4: Japanese Patent Application Publication No. 2019-104869 Summary of the invention
[0010] Technical issues to be solved by the invention
[0011] At the mass production site, the adhesive film for circuit connection is sometimes placed in the form of a reel, and sometimes it deteriorates due to drying, and the adhesion deteriorates. In addition, in order to prevent this drying deterioration, it is also studied to form a laminate by laminating a substrate on both sides of the adhesive film. The substrate of this laminate may sometimes peel off due to a slight impact during transportation, and may also peel off when the laminate is cut into a size suitable for use. Moreover, even when it is used, a part of the adhesive film may be transferred to the substrate when the substrate is removed, resulting in an undesirable situation in which it cannot be used as a product.
[0012] One aspect of the present invention is to provide a laminated body that suppresses deterioration caused by drying of a circuit connection adhesive film and is less likely to cause peeling of a substrate during transportation and cutting, and to prevent problems when the substrate is peeled off during use. Another aspect of the present invention is to provide a method for manufacturing the laminated body. Another aspect of the present invention is to provide a method for manufacturing a connection structure using the laminated body.
[0013] Means for solving technical problems
[0014] Some aspects of the present invention provide [1] to [9] shown below.
[0015] [1] A laminate comprising a first substrate, an adhesive film for circuit connection provided on the first substrate, and a second substrate provided on the adhesive film, wherein, when the adhesion strength of the first substrate to the adhesive film is set to P1 and the adhesion strength of the second substrate to the adhesive film is set to P2, P1 / P2 is 0.25 to 0.80.
[0016] [2] The laminate according to [1], wherein the adhesive film is a conductive adhesive film containing conductive particles.
[0017] [3] The laminate according to [2], wherein the adhesive film has a first adhesive layer containing conductive particles and a second adhesive layer containing no conductive particles.
[0018] [4] The laminate according to [3], wherein the first substrate is adjacent to the first adhesive layer, and the second substrate is adjacent to the second adhesive layer.
[0019] [5] The laminate according to any one of [1] to [4], wherein the adhesive film contains a heat-reactive component and a curing agent.
[0020] [6] The laminate according to any one of [1] to [5], wherein the adhesion strength P1 is 0.5 to 15 N / m, and the adhesion strength P2 is 1.5 to 30 N / m.
[0021] [7] The laminate according to any one of [1] to [6], wherein the first substrate is a substrate having a surface in contact with the adhesive film subjected to a release treatment.
[0022] [8] A method for manufacturing a laminate, comprising a first substrate of the laminate, an adhesive film for circuit connection arranged on the first substrate, and a second substrate arranged on the adhesive film, the method for manufacturing the laminate comprising the following steps: preparing the first substrate, the second substrate, and the adhesive film or a material for forming the adhesive film in such a manner that when the adhesion strength of the first substrate relative to the adhesive film is set to P1 and the adhesion strength of the second substrate relative to the adhesive film is set to P2, P1 / P2 becomes 0.25 to 0.80; and obtaining the laminate by arranging or forming the adhesive film between the first substrate and the second substrate.
[0023] [9] A method for manufacturing a connection structure, the connection structure comprising a first circuit component having a first electrode, a second circuit component having a second electrode, and a connection portion arranged between the first circuit component and the second circuit component and electrically connecting the first electrode and the second electrode to each other, wherein the method for manufacturing the connection structure comprises the following steps: removing the first substrate from the stacked body according to any one of [1] to [7], and arranging the remaining portion of the stacked body on the first circuit component in such a manner that the surface of the adhesive film in contact with the first substrate and the surface of the first circuit component provided with the first electrode are in contact; removing the second substrate from the remaining portion of the stacked body, and arranging the second circuit component on the adhesive film in such a manner that the surface of the adhesive film in contact with the second substrate and the surface of the second circuit component provided with the second electrode are in contact; and thermally pressing the first circuit component and the second circuit component to electrically connect the first electrode and the second electrode to each other.
[0024] Effects of the Invention
[0025] According to one aspect of the present invention, a laminate can be provided, which suppresses deterioration caused by drying of an adhesive film for circuit connection and is less likely to cause peeling of the substrate during transportation and cutting, and the inconvenience of peeling the substrate during use. In addition, according to some other aspects of the present invention, a method for manufacturing the above-mentioned laminate and a method for manufacturing a connection structure using the above-mentioned laminate are provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic cross-sectional view showing a laminated body according to one embodiment of the present invention.
[0027] Figure 2 It is a schematic cross-sectional view for explaining the method of measuring the close contact strength P1.
[0028] Figure 3 It is a schematic cross-sectional view for explaining the method of measuring the close contact strength P2.
[0029] Figure 4 Yes Description Figure 1 A schematic cross-sectional view of one embodiment of a method for producing a laminate.
[0030] Figure 5 Yes Description Figure 1 A schematic cross-sectional view of another embodiment of a method for producing a laminate.
[0031] Figure 6 This is a schematic cross-sectional view showing a connection structure according to an embodiment of the present invention.
[0032] Figure 7 Yes means Figure 6 Schematic cross-sectional view of a method for manufacturing a connection structure. DETAILED DESCRIPTION
[0033] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings as appropriate. In addition, the present invention is not limited to the following embodiments.
[0034] In the numerical range described in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment. In addition, the lower limit and upper limit of the numerical range can be arbitrarily combined with the lower limit or upper limit of other numerical ranges. In the expression of the numerical range "A to B", the numerical values A and B at both ends are included in the numerical range as the lower limit and upper limit, respectively.
[0035] <Laminated body>
[0036] A laminate according to one embodiment of the present invention comprises a first substrate, an adhesive film for circuit connection arranged on the first substrate, and a second substrate arranged on the adhesive film, wherein, when the adhesion strength of the first substrate relative to the adhesive film is set to P1 and the adhesion strength of the second substrate relative to the adhesive film is set to P2, P1 / P2 is 0.25 to 0.80.
[0037] Figure 1 This is a schematic cross-sectional view showing one embodiment of a laminate. Figure 1 The laminate 1 shown includes a first substrate 2, an adhesive film 3 for circuit connection provided on the first substrate 2 (hereinafter, also simply referred to as "adhesive film 3"), and a second substrate 4 provided on the adhesive film 3. In the laminate 1, when the adhesion strength of the first substrate 2 to the adhesive film 3 is set to P1 and the adhesion strength of the second substrate 4 to the adhesive film 3 is set to P2, P1 / P2 becomes 0.25 to 0.80.
[0038] Figure 2 and Figure 3The following are schematic cross-sectional views for explaining the measuring method of the adhesion strengths P1 and P2. The adhesion strengths P1 and P2 are measured by the following methods. In addition, the conditions not described below are based on JIS K6854-1.
[0039] [Measurement method of adhesion strength P1]
[0040] First, a cutout (slit) is formed in the first substrate 2. The shape of the cutout is, for example, a rectangle, and the size of the cutout is, for example, 1.5 mm in length×40 mm in width.
[0041] Next, one side of the double-sided tape 8 is attached to the second substrate 4 of the laminate 1, and the other side of the double-sided tape 8 is attached to the slide glass 9, thereby fixing the laminate 1 on the slide glass 9 to obtain a measurement sample. The thickness of the double-sided tape is, for example, 0.13 mm, and the thickness of the slide glass 9 is, for example, 1.3 mm.
[0042] Next, the obtained measurement sample is placed on the hot plate 10 at 40° C. from the slide glass side.
[0043] Next, using a tensile tester (e.g., TENSILON manufactured by A&D Company, Limited), the stripping speed is 50 mm / min and the stripping angle is 90°. Figure 2 The first substrate 2 is stretched in the direction indicated by the arrow X in the figure to peel the first substrate 2 from the adhesive film 3 in the longitudinal direction, and the adhesion strength of the first substrate 2 with respect to the adhesive film 3 is measured.
[0044] [Method for measuring adhesion strength P2]
[0045] First, prepare a pressure-sensitive adhesive film 11. The pressure-sensitive adhesive film 11 is, for example, a film in which a pressure-sensitive adhesive layer is formed on a film-like substrate (for example, a polyimide film). As a pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer, any pressure-sensitive adhesive that can bond the pressure-sensitive adhesive film 11 to the adhesive film 3 without peeling off at the interface between the pressure-sensitive adhesive film 11 and the adhesive film 3 when measuring the adhesion strength P2 will suffice. The shape of the pressure-sensitive adhesive film 11 is, for example, a rectangle, and the size of the pressure-sensitive adhesive film 11 is, for example, 10 mm in length and 40 mm in width. As the pressure-sensitive adhesive film, for example, PI tape (No. 1030) manufactured by OKAMOTO INDUSTRIES, INC. can be used.
[0046] Next, after the first substrate 2 is peeled off from the laminate 1, the pressure-sensitive adhesive film 11 is disposed on the surface of the adhesive film 3 on which the first substrate 2 is disposed from the pressure-sensitive adhesive layer side. Figure 3As shown in the figure, in order to hold one end of the pressure-sensitive adhesive film 11, a part of the pressure-sensitive adhesive film 11 is arranged on the surface of the adhesive film 3. At the same time, one side of the double-sided tape 8 is attached to the second substrate 4 of the above-mentioned laminate 1, and the other side of the double-sided tape 8 is attached to the slide glass 9, so that the laminate 1 is fixed on the slide glass 9. Through the above operation, a measurement sample is obtained. In addition, the double-sided tape 8 and the slide glass 9 can use the same type of double-sided tape and slide glass used when measuring the adhesion strength P1.
[0047] Next, the obtained measurement sample is placed on a hot plate 10 at 40° C. from the slide glass 9 side.
[0048] Next, using a tensile tester (e.g., TENSILON manufactured by A&D Company, Limited), the stripping speed is 50 mm / min and the stripping angle is 90°. Figure 3 The pressure-sensitive adhesive film 11 is stretched in the direction indicated by the arrow Y in the middle, thereby peeling the adhesive film 3 from the second substrate 4 in the longitudinal direction, and the adhesion strength of the second substrate 4 with respect to the adhesive film 3 is measured.
[0049] The measurement of the above-mentioned adhesion strengths P1 and P2 was started 10 seconds after the measurement sample was placed on the hot plate. In addition, the adhesion strength was measured at three randomly selected locations in the laminate, and the arithmetic mean of the adhesion strengths obtained at the three locations was used. In addition, since the measured values of the adhesion strength tend to deviate immediately after the measurement starts, the maximum value of the measured values obtained 1 to 3 seconds after the measurement starts was used in the calculation of the adhesion strength P1, and the minimum value of the measured values obtained 1 to 3 seconds after the measurement starts was used in the calculation of the adhesion strength P2.
[0050] In the laminate 1, since both sides of the adhesive film 3 are covered by the substrate (the first substrate and the second substrate), it is difficult for the adhesive film 3 to be deteriorated due to drying. In addition, since the ratio of the adhesion strength (P1 / P2) is within the above range, it is difficult for the substrate to be peeled off during transportation and cutting, and it is difficult for the substrate to be peeled off during use.
[0051] From the viewpoint of more easily obtaining the above-mentioned effect, the ratio (P1 / P2) of the above-mentioned close contact strength may be 0.30 or more, 0.40 or more, or 0.50 or less, or 0.75 or less, or 0.30 to 0.75, 0.40 to 0.75, or 0.50 to 0.65.
[0052] From the viewpoint of further facilitating the above-mentioned effects, the adhesion strength P1 may be 0.5 to 15 N / m, and the adhesion strength P2 may be 1.5 to 30 N / m. From the viewpoint of further suppressing the peeling of the substrate during transportation and cutting, and the undesirable situation when the substrate is peeled off during use, the adhesion strength P1 may also be 1.0 to 15 N / m, 1.5 to 6.0 N / m, or 2.5 to 4.5 N / m. From the viewpoint of further suppressing the peeling of the substrate during transportation and cutting, and the undesirable situation when the substrate is peeled off during use, the adhesion strength P2 may also be 2 to 30 N / m, 5 to 25 N / m, or 10 to 15 N / m. The above-mentioned adhesion strength can be adjusted by changing the constituent material of the substrate, changing the type of demolding treatment of the substrate, changing the constituent material of the adhesive film, etc.
[0053] From the viewpoint of more easily obtaining the above-mentioned effect, the difference (P2-P1) between the close contact strength P1 and the close contact strength P2 may be 1.5 to 8.0, 2.0 to 8.0, or 2.0 to 6.0.
[0054] (First substrate and second substrate)
[0055] The first substrate 2 and the second substrate 4 may be the same substrate or different substrates. For example, the first substrate 2 and the second substrate 4 may be made of stretched polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefin, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubber, liquid crystal polymer, etc. (e.g., film). When polyethylene terephthalate is used, the drying of the adhesive film can be further suppressed.
[0056] The surfaces of the first substrate 2 and the second substrate 4 (the surfaces in contact with the adhesive film) may be subjected to a release treatment. For example, one or both of the first substrate 2 and the second substrate 4 may be substrates formed of the above-mentioned materials and subjected to a release treatment on the surface. Examples of the release treatment include surface treatment with silicone or a fluorine compound.
[0057] The first substrate 2 and the second substrate 4 are selected to obtain the above ratio P1 / P2. Among the above substrates, if the first substrate 2 is a substrate whose surface in contact with the adhesive film is subjected to a demolding treatment, the above ratio P1 / P2 is easy to obtain, and if both the first substrate 2 and the second substrate 4 are substrates whose surfaces in contact with the adhesive film are subjected to a demolding treatment, the above ratio P1 / P2 is even easier to obtain.
[0058] The thickness of the first substrate 2 may be 5 to 150 μm, or may be 25 to 100 μm, or 35 to 55 μm.
[0059] The thickness of the second substrate 4 may be 5 to 150 μm, or 25 to 100 μm, or 35 to 55 μm.
[0060] (Adhesive film)
[0061] The adhesive film 3 includes a first adhesive layer 6 containing conductive particles 5 and a second adhesive layer 7 not containing conductive particles. The first adhesive layer 6 and the second adhesive layer 7 are respectively arranged so that the first substrate 2 is adjacent to the first adhesive layer 6, and the second substrate 4 is adjacent to the second adhesive layer 7. The first adhesive layer 6 is formed of a first adhesive composition, and the second adhesive layer 7 is formed of a second adhesive composition. The constituent components of the first adhesive layer 6 and the second adhesive layer 7 are described below. In the following description, "the first adhesive layer 6" can be replaced by "the first adhesive composition", and "the second adhesive layer 7" can be replaced by "the second adhesive composition".
[0062] [First adhesive layer]
[0063] The first adhesive layer 6 contains an adhesive component and conductive particles 5 dispersed in the adhesive component. In this specification, "adhesive component" refers to the components constituting the adhesive layer except for the conductive particles. The adhesive component contains, for example, a heat-reactive component and a curing agent, and may also contain a film-forming component, a non-conductive filler, a coupling agent, etc.
[0064] (a) Conductive particles
[0065] The conductive particles 5 are not particularly limited as long as they are conductive particles, and may be metal particles composed of metals such as Au, Ag, Pd, Ni, Cu, solder, conductive carbon particles composed of conductive carbon, etc. The conductive particles 5 may be coated conductive particles, which have: a core comprising non-conductive glass, ceramics, plastic (polystyrene, etc.) and a coating layer comprising the above metal or the above conductive carbon and coating the core. The conductive particles 5 may be used alone or in combination of multiple conductive particles.
[0066] From the viewpoint of excellent dispersibility and conductivity, the average particle size of the conductive particles 5 can be 1.0 μm or more, 2.0 μm or more, 2.5 μm or more, or 3.0 μm or more. From the viewpoint of excellent dispersibility and conductivity, the average particle size of the conductive particles 5 can be 20.0 μm or less, 10.0 μm or less, 7.0 μm or less, or 5.0 μm or less. From these viewpoints, the average particle size of the conductive particles 5 can be, for example, 1.0 to 20.0 μm. In this specification, for 300 (pcs) conductive particles randomly selected from the first adhesive layer 6, the particle size is measured by observation using a scanning electron microscope (SEM), and the average value of the obtained particle size is taken as the average particle size.
[0067] From the viewpoint of being able to further improve the conductivity, the content of the conductive particles 5 in the first adhesive layer 6 may be 1% by mass or more, 5% by mass or more, or 10% by mass or more, based on the total mass of the first adhesive layer 6. From the viewpoint of easily suppressing short circuits, the content of the conductive particles 5 in the first adhesive layer 6 may be 60% by mass or less, 50% by mass or less, or 40% by mass or less, based on the total mass of the first adhesive layer 6. From these viewpoints, the content of the conductive particles 5 in the first adhesive layer 6 may be, for example, 1 to 60% by mass, based on the total mass of the first adhesive layer 6.
[0068] (b) Thermally reactive components
[0069] The heat-reactive component is a component that reacts with the curing agent under heating. From the viewpoint of achieving a more excellent effect of reducing connection resistance, the heat-reactive component may be a cationically polymerizable compound.
[0070] From the viewpoint of further improving the effect of reducing the connection resistance and improving the connection reliability, the cationic polymerizable compound may be a compound having a cyclic ether group. Among the compounds having a cyclic ether group, when at least one selected from the group consisting of alicyclic epoxy compounds and oxetane compounds is used, there is a tendency that the effect of reducing the connection resistance is further improved.
[0071] The alicyclic epoxy compound can be used without particular limitation as long as it is a compound having an alicyclic epoxy group (for example, an epoxycyclohexyl group), but when bis-7-oxabicyclo[4.1.0]heptane is used, the above-mentioned adhesion strength P1 is easily obtained. As commercially available products of alicyclic epoxy compounds, in addition to CELLOXIDE 8010 (trade name, bis-7-oxabicyclo[4.1.0]heptane, manufactured by Daicel Corporation), for example, EHPE 3150, EHPE 3150CE, CELLOXIDE 2021P, CELLOXIDE 2081 (trade name, manufactured by Daicel Corporation) and the like can also be cited. They can be used alone or in combination of multiple compounds. From the viewpoint of easily obtaining the desired melt viscosity, the cationic polymerizable compound can contain both an alicyclic epoxy compound and an oxetane compound.
[0072] As long as the oxetane compound is a compound having an oxetane group, it can be used without particular limitation, but when 4,4'-bis[(3-ethyl-3-oxetane)methoxymethyl]biphenyl is used, the above-mentioned adhesion strength P1 is easily obtained. As commercially available products of oxetane compounds, for example, ETERNACOLL OXBP (trade name, 4,4'-bis[(3-ethyl-3-oxetane)methoxymethyl]biphenyl, manufactured by Ube Industries, Ltd.), OXSQ, OXT-121, OXT-221, OXT-101, OXT-212 (trade name, manufactured by TOAGOSEI CO., LTD.), etc. can be cited. One compound can be used alone, or a plurality of compounds can be used in combination.
[0073] From the viewpoint of ensuring the curability of the first adhesive layer 6, the content of the heat-reactive component in the first adhesive layer 6 may be 5% by mass or more, 10% by mass or more, 15% by mass or more, or 20% by mass or more, based on the total mass of the first adhesive layer 6. From the viewpoint of ensuring the formability of the first adhesive layer 6, the content of the heat-reactive component in the first adhesive layer 6 may be 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less, based on the total mass of the first adhesive layer 6. From these viewpoints, the content of the heat-reactive component in the first adhesive layer 6 may be, for example, 5 to 70% by mass, based on the total mass of the first adhesive layer 6.
[0074] (c) Curing agent
[0075] The curing agent reacts with the heat-reactive component to cure the first adhesive layer 6. When a cationically polymerizable compound is used as the heat-reactive component, a thermal cationic polymerization initiator that generates an acid or the like by heating to initiate polymerization can be used as the curing agent.
[0076] The thermal cationic polymerization initiator may be a salt compound composed of a cation and an anion. Examples of the salt compound include BF 4- , BR 4- (R represents a phenyl group substituted with two or more fluorine atoms or two or more trifluoromethyl groups.) PF 6- , SbF 6- , AsF 6- Onium salts such as sulfonium salts, phosphonium salts, ammonium salts, diazonium salts, iodonium salts, anilinium salts, pyridinium salts, etc. having an anion, etc. These may be used alone or in combination of two or more.
[0077] From the viewpoint of storage stability, the thermal cationic polymerization initiator may be a salt compound having an anion containing boron as a constituent element. 4- or BR 4- (R represents a phenyl group substituted with two or more fluorine atoms or two or more trifluoromethyl groups.) has a tendency to have higher storage stability. 4- If the thermal cationic polymerization initiator is a salt compound having tetrakis(pentafluorophenyl)borate, there is a tendency for the storage stability to be further increased. If the thermal cationic polymerization initiator is a salt compound having tetrakis(pentafluorophenyl)borate, there is a tendency for the storage stability to be particularly high. In addition, from the viewpoint of having resistance to substances that may cause curing hindrance to cationic curing, the thermal cationic polymerization initiator may be an aniline salt (for example, an aniline salt having an anion containing boron as a constituent element). As an aniline salt, for example, N,N-dimethylaniline salt, N,N-diethylaniline salt and other N,N-dialkylaniline salts can be cited. As a commercial product of such a salt compound, for example, CXC-1821 (trade name, manufactured by King Industries) can be cited.
[0078] From the viewpoint of ensuring the formability and curability of the first adhesive layer 6, the content of the curing agent in the first adhesive layer 6 can be, for example, 0.1 to 20 parts by mass, 1 to 18 parts by mass, 3 to 15 parts by mass, or 5 to 12 parts by mass relative to 100 parts by mass of the heat-reactive component in the first adhesive layer 6.
[0079] (d) Film-forming components
[0080] The film-forming component contributes to the formability (shape retention) of the first adhesive layer 6. Examples of the film-forming component include phenoxy resins, polyester resins, polyamide resins, polyurethane resins, polyester urethane resins, acrylic rubbers, epoxy resins (solid at 25°C), etc. They can be used alone or in combination. Based on the total mass of the first adhesive layer 6, the content of the film-forming component in the first adhesive layer 6 can be 1% by mass or more, 5% by mass or more, or 10% by mass or more, and can be 70% by mass or less, 50% by mass or less, or 30% by mass or less, and can be 1 to 70% by mass, 5 to 50% by mass, or 10 to 30% by mass.
[0081] (e) Non-conductive filler
[0082] The non-conductive filler may be any of a non-conductive inorganic filler and an organic filler. As inorganic fillers, for example, metal oxide particles such as silica particles, alumina particles, silica-alumina particles, titanium dioxide particles, zirconium oxide particles; inorganic particles such as metal nitride particles. As organic fillers, for example, organic particles such as silicone particles, methacrylate-butadiene-styrene particles, acrylic-silicone particles, polyamide particles, and polyimide particles can be mentioned. They can be used alone or in combination. Based on the total mass of the first adhesive layer 6, the content of the non-conductive filler in the first adhesive layer 6 can be 0.1 to 10% by mass.
[0083] (f) Coupling agent
[0084] The coupling agent helps to further improve the adhesion. As the coupling agent, for example, silane coupling agents having organic functional groups such as (meth)acryloyl, mercapto, amino, imidazole, epoxy, silane compounds such as tetraalkoxysilane, tetraalkoxy titanate derivatives, polydialkyl titanate derivatives, etc. can be cited. They can be used alone or in combination. Based on the total mass of the first adhesive layer 6, the content of the coupling agent in the first adhesive layer 6 can be 0.1 to 10% by mass.
[0085] (g) Other additives
[0086] In addition to the above components, the first adhesive layer 6 may also contain other additives such as a softener, an accelerator, an anti-degradation agent, a colorant, a flame retardant, a thixotropic agent, etc. Based on the total mass of the first adhesive layer 6, the content of other additives in the first adhesive layer 6 may be, for example, 0.1 to 10 mass %.
[0087] The thickness of the first adhesive layer 6 may be 3 μm or more or 10 μm or more, or 30 μm or less or 20 μm or less.
[0088] [Second Adhesive Layer]
[0089] In addition to not containing the conductive particles 5, the second adhesive layer 7 may contain the same components as the components that the first adhesive layer 6 may contain. For example, the second adhesive layer 7 may contain a heat-reactive component, a curing agent, a film-forming component, a non-conductive filler, and a coupling agent. The components contained in the second adhesive layer 7 may be the same as or different from those contained in the first adhesive layer 6. As in the case of the first adhesive layer 6, when at least one selected from the group consisting of alicyclic epoxy compounds and oxetane compounds is used as a heat-reactive component, there is a tendency that the effect of reducing the connection resistance is further improved. In addition, when at least one selected from the group consisting of alicyclic epoxy compounds and oxetane compounds is used as a heat-reactive component, it is easy to obtain the above-mentioned adhesion strength P2, and when at least one selected from the group consisting of bis-7-oxabicyclo[4.1.0]heptane and 4,4'-bis[(3-ethyl-3-oxetane)methoxymethyl]biphenyl is used, it is easier to obtain the above-mentioned adhesion strength P2.
[0090] From the viewpoint of ensuring the curability of the second adhesive layer 7, the content of the heat-reactive component in the second adhesive layer 7 may be 5% by mass or more, 10% by mass or more, 15% by mass or more, or 20% by mass or more, based on the total mass of the second adhesive layer 7. From the viewpoint of ensuring the formability of the second adhesive layer 7, the content of the heat-reactive component in the second adhesive layer 7 may be 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less, based on the total mass of the second adhesive layer 7. From these viewpoints, the content of the heat-reactive component in the second adhesive layer 7 may be, for example, 5 to 70% by mass, based on the total mass of the second adhesive layer 7.
[0091] From the viewpoint of ensuring the formability and curability of the second adhesive layer 7, the content of the curing agent in the second adhesive layer 7 can be, for example, 0.1 to 20 parts by mass, 1 to 18 parts by mass, 3 to 15 parts by mass, or 5 to 12 parts by mass relative to 100 parts by mass of the heat-reactive component in the second adhesive layer 7.
[0092] Based on the total mass of the second adhesive layer 7, the content of the film-forming component in the second adhesive layer 7 can be greater than 1 mass %, greater than 3 mass % or greater than 5 mass %, can be less than 60 mass %, less than 40 mass % or less than 20 mass %, and can be 1-60 mass %, 3-40 mass % or 5-20 mass %.
[0093] Based on the total mass of the second adhesive layer 7, the content of the non-conductive filler in the second adhesive layer 7 can be greater than 1 mass %, greater than 10 mass % or greater than 30 mass %, can be less than 90 mass %, less than 70 mass % or less than 50 mass %, and can be 1-90 mass %, 10-70 mass % or 30-50 mass %.
[0094] The content of the coupling agent in the second adhesive layer 7 may be 0.1 to 10% by mass based on the total mass of the second adhesive layer 7 .
[0095] The thickness of the second adhesive layer 7 may be 3 μm or more or 10 μm or more, 30 μm or less or 20 μm or less, and may be 3 to 30 μm or 10 to 20 μm.
[0096] The total thickness of the adhesive film 3 may be 6 μm or more or 20 μm or more, 60 μm or less or 40 μm or less, and may be 6 to 60 μm or 20 to 40 μm.
[0097] The adhesive film 3 may be a conductive adhesive film having anisotropic conductivity (anisotropic conductive film) or a conductive adhesive film not having anisotropic conductivity.
[0098] As mentioned above, although the laminated body 1 of one embodiment was demonstrated, the laminated body of this invention is not limited to the said embodiment.
[0099] For example, the first adhesive layer 6 and the second adhesive layer 7 in the adhesive film 3 may be arranged such that the first substrate 2 and the second adhesive layer 7 are adjacent to each other and the second substrate 4 and the first adhesive layer 6 are adjacent to each other.
[0100] Furthermore, for example, the adhesive film 3 may be a single-layer adhesive film formed of only the first adhesive layer 6. Furthermore, for example, the adhesive film 3 may be a multi-layer adhesive film formed of three or more adhesive layers.
[0101] Furthermore, for example, the adhesive film 3 may not contain the conductive particles 5 .
[0102] <Method for producing laminate>
[0103] Another embodiment of the present invention relates to a method for manufacturing a laminated body having a first substrate, an adhesive film for circuit connection disposed on the first substrate, and a second substrate disposed on the adhesive film, wherein the method for manufacturing the laminated body has the following steps: preparing the first substrate, the second substrate, and the adhesive film or a material for forming the adhesive film in such a manner that the adhesion strength of the first substrate relative to the adhesive film is set to P1 and the adhesion strength of the second substrate relative to the adhesive film is set to P2, and P1 / P2 becomes 0.25 to 0.80 (hereinafter referred to as the "preparation step"); and obtaining a laminated body by arranging or forming an adhesive film between the first substrate and the second substrate (hereinafter referred to as the "lamination step"). The following describes each step. In addition, the details of the first substrate, the second substrate, the adhesive film, and the material for forming the adhesive film are the same as those described for the laminated body 1.
[0104] (Preparation process)
[0105] In the preparation step, the first substrate, the second substrate, and the adhesive film or a material for forming the adhesive film are prepared so that P1 / P2 is 0.25 to 0.80. When the adhesive film is prepared in the preparation step, the preparation step may include a step of forming the adhesive film.
[0106] The process of forming the adhesive film includes, for example, a process (A) of forming a first adhesive layer and a process (B) of forming a second adhesive layer. In process (A), for example, a solution of the first adhesive composition (first varnish composition) is first prepared by mixing the components (conductive particles, heat-reactive components, curing agent, etc.) that may be included in the first adhesive layer in an organic solvent. Then, the first varnish composition is applied to the substrate subjected to the demolding treatment using a knife coater, a roll coater, an applicator, a comma coater, a die coater, etc. to form a layer formed by the first varnish composition, and then the organic solvent is volatilized by heating to form the first adhesive layer on the substrate. At this time, the thickness of the first adhesive layer finally obtained can be adjusted by adjusting the coating amount of the first varnish composition.
[0107] The organic solvent used in the preparation of the first varnish composition is not particularly limited as long as it has the property of being able to uniformly dissolve or disperse each component. As such an organic solvent, for example, toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, propyl acetate, butyl acetate, etc. can be cited. These organic solvents can be used alone or in combination of two or more. Mixing (stirring mixing or kneading) when preparing the first varnish composition can be carried out, for example, using a stirrer, a grinder, a three-roll mill, a ball mill, a bead mill, a homogenizing disperser, etc.
[0108] As long as substrate has the heat resistance that can withstand the heating conditions when making organic solvent volatilize, there is no particular restriction. As this substrate, for example, the substrate (for example, film) formed by stretched polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefin, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubber, liquid crystal polymer etc. can be used.
[0109] The heating conditions for volatilizing the organic solvent from the first varnish composition applied on the substrate can be appropriately set according to the organic solvent used, etc. The heating conditions may be, for example, heating at 40 to 120° C. for 0.1 to 10 minutes.
[0110] In step (B), the second adhesive layer can be formed in the same manner as in step (A), except that a solution of the second adhesive composition (second varnish composition) is prepared by mixing the components that may be contained in the second adhesive layer (thermoreactive component, curing agent, etc.) in an organic solvent, and the second varnish composition is used instead of the first varnish composition.
[0111] In the above method, in step (B), the second adhesive layer can be formed by applying the second varnish composition on the first adhesive layer or the first varnish composition obtained in step (A) and drying it, thereby obtaining an adhesive film. In addition, when step (A) is performed after step (B), the first adhesive layer can be formed by applying the first varnish composition on the second adhesive layer or the second varnish composition and drying it, thereby obtaining an adhesive film. In addition, in steps (A) and (B), when the first adhesive layer and the second adhesive layer are formed on different substrates by applying the first varnish composition and the second varnish composition on different substrates and drying them, the adhesive film can be obtained by laminating them.
[0112] Examples of the method for laminating the first adhesive layer and the second adhesive layer include heat pressing, roll lamination, vacuum lamination, etc. Lamination can be performed under a temperature condition of 0 to 80°C, for example.
[0113] (Lamination process)
[0114] In the lamination step, when an adhesive film is prepared in the preparation step, the laminate is obtained by arranging the adhesive film between the first substrate and the second substrate. Also, when a material for forming an adhesive film is prepared in the preparation step, the laminate is obtained by forming the adhesive film between the first substrate and the second substrate.
[0115] The lamination step may be a step of placing or forming an adhesive film between the first substrate and the second substrate by a method including a step of placing or forming an adhesive film on one of the first substrate and the second substrate and a step of placing the other of the first substrate and the second substrate on the adhesive film. Figure 4 As shown, the laminate 1 can be obtained by sequentially forming the first adhesive layer 6 and the second adhesive layer 7 on the first substrate 2 to form the adhesive film 3 on the first substrate 2 and then disposing the second substrate 4 on the adhesive film 3 (on the second adhesive layer 7 ).
[0116] The lamination step may be a step of forming an adhesive film between the first substrate and the second substrate by a method including a step of forming a first adhesive layer on one of the first substrate and the second substrate to obtain a first laminated film, a step of forming a second adhesive layer on the other of the first substrate and the second substrate to obtain a second laminated film, and a step of laminating the first laminated film and the second laminated film in a manner that the first adhesive layer and the second adhesive layer are opposed to each other. For example, in the case of manufacturing the laminated body 1, as Figure 5 As shown, after forming the first adhesive layer 6 on the first substrate 2 to obtain the first laminate film 12, and forming the second adhesive layer 7 on the second substrate 4 to obtain the second laminate film 13, these laminate films are laminated in a manner such that the first adhesive layer 6 and the second adhesive layer 7 face each other to obtain the laminated body 1.
[0117] In any of the above methods, the adhesive film 3 can be formed by the method described in the preparation step except that the first substrate or the second substrate is used as the substrate.
[0118] <Connection structure>
[0119] A connection structure according to another embodiment of the present invention comprises: a first circuit component having a first electrode, a second circuit component having a second electrode, and a connection portion disposed between the first circuit component and the second circuit component and electrically connecting the first electrode and the second electrode to each other. The connection portion comprises a cured product of the circuit connection adhesive film in the laminate.
[0120] Figure 6 This is a schematic cross-sectional view showing one embodiment of a connection structure. Figure 6 The connection structure 20 shown includes: a first circuit member 21 and a second circuit member 24 facing each other; and a connection portion 27 between the first circuit member 21 and the second circuit member 24 .
[0121] The first circuit member 21 includes a first circuit board 22 and a first electrode 23 formed on a principal surface 22a of the first circuit board 22. The second circuit member 24 includes a second circuit board 25 and a second electrode 26 formed on a principal surface 25a of the second circuit board 25.
[0122] The first circuit component 21 and the second circuit component 24 are not particularly limited as long as they are components formed with electrodes that need to be electrically connected. As components (circuit components, etc.) formed with electrodes, inorganic substrates such as semiconductors, glass, and ceramics; polyimide substrates represented by TCP, FPC, COF, etc.; substrates formed with electrodes on films such as polycarbonate, polyester, and polyethersulfone; printed wiring boards, etc., can be used, and a combination of multiple of them can also be used.
[0123] The connection portion 27 includes a cured product of the adhesive film 1. The connection portion 27 includes, for example, a first region 28 located on the first circuit component 21 side in the direction in which the first circuit component 21 and the second circuit component 24 are opposite to each other; a second region 29 located on the second circuit component 24 side in the above direction (the direction in which the first circuit component 21 and the second circuit component 24 are opposite to each other); and conductive particles 5 interposed at least between the first electrode 23 and the second electrode 26 and electrically connecting the first electrode 23 and the second electrode 26 to each other. The first region 28 is, for example, a region in which the portion other than the conductive particles of the first adhesive layer 6 is cured. The second region 29 is, for example, a region in which the second adhesive layer 7 is cured.
[0124] <Method for producing a connection structure>
[0125] A method for manufacturing a connection structure involved in another embodiment of the present invention is a method for manufacturing a connection structure comprising a first circuit component having a first electrode, a second circuit component having a second electrode, and a connection portion arranged between the first circuit component and the second circuit component and electrically connecting the first electrode and the second electrode to each other, wherein the method for manufacturing a connection structure comprises the following steps: removing the first substrate from the stacked body involved in the above-mentioned embodiment, and arranging the remaining part of the stacked body (the part where the first substrate is removed from the stacked body) on the first circuit component in a manner that the surface of the adhesive film in contact with the first substrate and the surface of the first circuit component provided with the first electrode are in contact (hereinafter referred to as the "first arrangement step"); removing the second substrate from the remaining part of the stacked body, and arranging the second circuit component on the adhesive film in a manner that the surface of the adhesive film in contact with the second substrate and the surface of the second circuit component provided with the second electrode are in contact; and hot pressing the first circuit component and the second circuit component to electrically connect the first electrode and the second electrode to each other.
[0126] Figure 7 Schematic cross-sectional view showing one embodiment of a method for manufacturing a connection structure. Figure 7 In the manufacturing method shown in the figure, firstly, the first circuit component 21 and the laminate 1 are prepared, and after the first substrate 2 is removed from the laminate 1, the remaining portion 30 of the laminate 1 is arranged on the first circuit component 21 in such a manner that the surface 3a of the adhesive film 3 in contact with the first substrate and the surface 21a of the first circuit component 21 provided with the first electrode 23 are in contact (refer to Figure 7 (a). At this time, as required, after the remaining portion 30 of the stacked body 1 is arranged or while the remaining portion 30 of the stacked body 1 is arranged, Figure 7 The pressure is applied in the directions indicated by arrows A1 and B1 in (a), and heating may also be performed while the pressure is applied.
[0127] By the above operation, the adhesive film 3 is temporarily connected to the first circuit member 21. In the case where the laminate 1 is configured in such a manner that the first base material 2 and the first adhesive layer 6 are adjacent to each other, as shown in FIG. Figure 7 As shown in (a), the first adhesive layer 6 of the adhesive film 3 is in contact with the first circuit member 21, and the number of conductive particles captured between the opposing electrodes can be increased.
[0128] Then, if Figure 7 As shown in (b), after removing the second substrate 4, the second circuit component 24 is arranged on the adhesive film 3 in such a manner that the surface 3b of the adhesive film 3 in contact with the second substrate 4 and the surface 24a of the second circuit component 24 provided with the second electrode 26 are in contact. Figure 7 The first circuit component 21 and the second circuit component 24 are thermally pressed in the directions indicated by arrows A2 and B2 in (b). As a result, the first electrode 23 and the second electrode 26 are electrically connected to each other, and the adhesive film 3 is cured to form a connecting portion 27, so that the first circuit component 21 and the second circuit component 24 are bonded via the connecting portion 27. As a result, the following is obtained. Figure 6 The connection structure 20 is shown.
[0129] Example
[0130] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to the following examples.
[0131] <Synthesis of phenoxy resin>
[0132] In a 3000 mL three-necked flask equipped with a Dimroth cooling tube, a calcium chloride tube, and a PTFE stirring rod connected to a stirring motor, 45 g of 4,4'-(9-fluorenyl)-diphenol (made by Sigma-Aldrich Japan KK) and 50 g of 3,3',5,5'-tetramethylbiphenol diglycidyl ether (made by Mitsubishi Chemical Corporation, YX-4000H) were dissolved in 1000 mL of N-methylpyrrolidone as a reaction solution. 21 g of potassium carbonate was added thereto, and the mixture was heated to 110°C with a mantle heater and stirred. After stirring for 3 hours, the reaction solution was added dropwise to a beaker containing 1000 mL of methanol, and the resulting precipitate was filtered by suction filtration. The filtered precipitate was washed three times with 300 mL of methanol to obtain 75 g of phenoxy resin P-1.
[0133] <Preparation of base material>
[0134] The following substrates 1 to 8 were prepared.
[0135] Substrate 1: A PET film with one side subjected to a release treatment (adhesion strength: 490 to 980 mN / 25 mm)
[0136] Substrate 2: A PET film with one side subjected to a release treatment (adhesion strength: 10 to 100 mN / 25 mm)
[0137] Substrate 3: A PET film having one surface subjected to a release treatment (adhesion strength: 980 to 1960 mN / 25 mm)
[0138] Substrate 4: A PET film with a release treatment applied to one side (adhesion strength: 200 to 600 mN / 25 mm)
[0139] Substrate 5: A PET film with a release treatment applied to one side (adhesion strength: 400 to 1200 mN / 25 mm)
[0140] Substrate 6: A7100 (manufactured by Toyobo Film Solutions Ltd., adhesion strength: 40 to 250 mN / 25 mm)
[0141] Substrate 7: A5300 (manufactured by Toyobo Film Solutions Ltd., adhesion strength: 500 to 1000 mN / 25 mm)
[0142] Substrate 8: A5400 (manufactured by Toyobo Film Solutions Ltd., adhesion strength: 100-400 mN / 25 mm)
[0143] The adhesion strength of the substrates 1 to 8 was measured by the following method.
[0144] First, a 31B pressure-sensitive adhesive tape made by Nitto Denko Corporation was pasted on the surface of the substrate (the surface formed by the demoulding treatment), and a reciprocating load was applied once with a crimping roller to obtain a laminated sample. The width of the pressure-sensitive adhesive tape was set to 25 mm. Then, the laminated sample was cut into a rectangle (a rectangle of 50 mm in width × 150 mm in length) in such a way that the length direction of the pressure-sensitive adhesive tape became the length direction. Then, using a double-sided tape, the cut laminated sample was attached to an aluminum plate from the substrate side for fixing. Then, the above-mentioned laminated sample fixed on the aluminum plate was fixed on a tensile testing machine, and the pressure-sensitive adhesive tape was peeled off from the substrate to the length direction under the conditions of a peeling speed of 300 mm / min and a peeling angle of 180 °, and the adhesion strength of the substrate relative to the pressure-sensitive adhesive tape was measured, and the maximum and minimum values of the measured values obtained 1 to 3 seconds after the start of the measurement were obtained. The above operation is performed at three randomly selected locations, and the arithmetic mean of the minimum values of the adhesion strength obtained at the three locations is taken as the minimum value of the above numerical range, and the arithmetic mean of the maximum values of the adhesion strength obtained at the three locations is taken as the maximum value of the above numerical range.
[0145] <Examples 1 to 5 and Comparative Examples 1 to 3>
[0146] (Preparation of Adhesive Composition)
[0147] The materials shown in Table 1 were mixed at the composition ratios shown in Table 1 (the numerical values in Table 1 represent the non-volatile content) to obtain a first adhesive composition and a second adhesive composition.
[0148] [Table 1]
[0149]
[0150] The details of the materials shown in Table 1 are as follows.
[0151] (a) Conductive particles
[0152] Conductive particles 1: Conductive particles having a polystyrene core and a palladium / nickel layer with a thickness of 0.1 μm on the surface (conductive particles having an average particle size of 3.0 μm and a specific gravity of 2.9)
[0153] (b) Thermally reactive components
[0154] OXBP: 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (difunctional oxetane compound, manufactured by Ube Industries, Ltd.)
[0155] · CEL8010: Bis-7-oxabicyclo[4.1.0]heptane (CELLOXIDE 8010, manufactured by Daicel Corporation)
[0156] (c) Curing agent
[0157] CXC-1821: A salt formed of a quaternary ammonium cation and a borate anion (thermal cationic polymerization initiator, manufactured by King Industries)
[0158] (d) Film-forming components
[0159] P-1: Phenoxy resin P-1 synthesized by the above method
[0160] ·YP-70: Phenoxy resin (manufactured by NIPPON STEEL Chemical & Material Co., Ltd.)
[0161] (e) Non-conductive filler
[0162] Silica particles 1: R805 (silica fine particles, manufactured by Evonik Industries AG), diluted with an organic solvent to a non-volatile content of 10% by mass
[0163] Silica particles 2: Surface-treated silica particles (hydrolysis product of silica and bis(trimethylsilyl)amine)
[0164] (f) Coupling agent
[0165] SH-6040: 3-Glycidoxypropyltrimethoxysilane (manufactured by Dow Corning Toray Co., Ltd.)
[0166] (Production of Laminated Body)
[0167] As the first substrate and the second substrate, the substrates shown in Table 2 were prepared. Next, by applying the first adhesive composition on the release-treated surface of the first substrate and drying it, a first laminated film having a first substrate and a first adhesive layer (thickness: 7 μm) formed on the first substrate was obtained. In addition, by applying the second adhesive composition on the release-treated surface of the second substrate and drying it, a second laminated film having a second substrate and a second adhesive layer (thickness: 9 μm) formed on the second substrate was obtained. Next, the obtained first laminated film and the second laminated film were laminated with a hot roll laminator heated to 50°C to obtain a laminated body having a first substrate, a first adhesive layer, a second adhesive layer and a second substrate in sequence.
[0168] (Measurement of Adhesion Strength)
[0169] use Figure 2 and Figure 3 The method exemplified here measures the adhesion strength P1 of the first substrate to the adhesive film (first adhesive layer) and the adhesion strength P2 of the second substrate to the adhesive film (second adhesive layer). The specific measurement method is as follows.
[0170] [Measurement method of adhesion strength P1]
[0171] First, a rectangular incision (slit) with a size of 1.5 mm in length and 40 mm in width was formed on the first substrate. Then, a double-sided tape (trade name: 11-583, manufactured by Showa Denko Materials Co., Ltd.) with a thickness of 0.13 mm and a glass slide with a thickness of 1.3 mm were prepared, and one side of the double-sided tape was attached to the second substrate of the laminate, and the other side of the double-sided tape was attached to the glass slide, thereby fixing the laminate on the glass slide to obtain a measurement sample. Then, the obtained measurement sample was arranged on a hot plate at 40°C from the glass slide side, and after 10 seconds from the start of the arrangement, the first substrate was stretched upward using a tensile tester (TENSILON, manufactured by A&D Company, Limited) at a peeling speed of 50 mm / min and a peeling angle of 90°, thereby peeling the first substrate from the adhesive film in the length direction, and the adhesion strength of the first substrate relative to the adhesive film was measured. The maximum value of the measured values obtained within 1 to 3 seconds after the start of the measurement was defined as the adhesion strength at the measurement site.
[0172] The above measurement was performed at three randomly selected locations, and the arithmetic mean of the adhesion strengths obtained at the three locations (the maximum value of the measured values obtained within 1 to 3 seconds after the start of the measurement) was taken as the adhesion strength P1.
[0173] [Method for measuring adhesion strength P2]
[0174] First, a rectangular pressure-sensitive adhesive film (PI tape, No. 1030, manufactured by OKAMOTO INDUSTRIES, INC.) with a size of 10 mm in length and 40 mm in width was prepared. Then, after peeling off the first substrate from the laminate, the pressure-sensitive adhesive film was arranged on the surface of the adhesive film on which the first substrate was arranged from the side of the pressure-sensitive adhesive layer, and a laminate with a pressure-sensitive adhesive film having a gripping portion at one end of the pressure-sensitive adhesive film was obtained. Next, a double-sided tape with a thickness of 0.13 mm (trade name: 11-583, manufactured by Showa Denko Materials Co., Ltd.) and a slide glass with a thickness of 1.3 mm were prepared, one side of the double-sided tape was attached to the second substrate of the laminate, and the other side of the double-sided tape was attached to the slide glass, thereby fixing the laminate on the slide glass to obtain a measurement sample. Next, the obtained measurement sample was arranged on a hot plate at 40°C from the slide glass side. Next, the pressure-sensitive adhesive film was pulled upward at a peeling speed of 50 mm / min and a peeling angle of 90° using a tensile tester (TENSILON, manufactured by A&D Company, Limited), thereby peeling the adhesive film from the second substrate in the longitudinal direction, and the adhesion strength of the second substrate to the adhesive film was measured. The minimum value of the measured values obtained within 1 to 3 seconds after the start of the measurement was taken as the adhesion strength of the above-mentioned measurement location.
[0175] The above measurement is performed at three randomly selected locations, and the arithmetic mean of the adhesion strengths obtained at the three locations (the minimum value of the measured values obtained within 1 to 3 seconds after the start of the measurement) is taken as the adhesion strength P2.
[0176] (Evaluation 1)
[0177] The obtained laminate was subjected to the following treatment (1) and then to the following treatment (2), and the states of the laminate after (1) and after (2) were evaluated.
[0178] (1) A rectangular slit of 1.5 mm × 40 mm in size is formed on the first substrate.
[0179] (2) Peeling off the first substrate
[0180] The evaluation criteria are shown below, and the results are shown in Table 2.
[0181] A (very good): No problem occurred at all during the slit and peeling of the first substrate.
[0182] B (good): Slight vibration occurred when the first substrate was peeled off (a phenomenon in which linear damage occurred along the short side direction of the adhesive film at a portion with locally high adhesion).
[0183] C (good): After the slits were formed, floating slightly occurred at the edge of the first substrate.
[0184] D (bad): When the first substrate was peeled off, lifting occurred at the interface between the second substrate and the adhesive film.
[0185] E (poor): The first substrate floats when a slight impact or a slit is formed.
[0186] (Rating 2)
[0187] Evaluation sample A was prepared by peeling off the first substrate from the laminate of Example 3, and evaluation sample B was prepared by forming a rectangular cut (slit) of 1.5 mm × 40 mm in the first substrate of the laminate of Example 3. Evaluation sample A is a sample in which the first adhesive layer is exposed, and evaluation sample B is a sample in which the first adhesive layer is protected by the first substrate.
[0188] Next, the evaluation samples A and B were placed in a 30°C constant temperature bath and dried for 4 hours using an electric blower. The evaluation samples A and B before and after the treatment were attached to the glass substrate from the first adhesive layer side using a thermocompression bonding device (LD-06, manufactured by OHASHI ENGINEERING Co., Ltd.) consisting of a workbench including a ceramic heater and a tool (8 mm × 50 mm). The attachment conditions were set to temperature: 70°C, pressure: 1 MPa, and pressurization time: 1 second. Next, the second substrate was peeled off, and a rectangular pressure-sensitive adhesive film (vinyl tape, No. 21S, manufactured by Nitto Denko Corporation) with a size of 1.3 mm × 40 mm was attached to the second adhesive layer. The pressure-sensitive adhesive film was stretched upward using a tensile tester (TENSILON, manufactured by A&D Company, Limited) at a peeling speed of 50 mm / min and a peeling angle of 90°, thereby peeling the adhesive film from the glass substrate, and the adhesion strength of the adhesive film (first adhesive layer) relative to the glass substrate was measured. The average value of the measured values obtained within 1 to 3 seconds after the start of the measurement was calculated, and the result was that in the evaluation sample A, the measured value before treatment was 85.8 N / m, while the adhesive film after treatment was not attached to the glass substrate, resulting in a result that could not be measured. On the other hand, in the evaluation sample B, the value before treatment was 74.0 N / m, and the value after treatment was 75.0 N / m, confirming that drying degradation was suppressed and adhesion strength was maintained.
[0189] [Table 2]
[0190]
[0191] Explanation of symbols
[0192] 1-laminate, 2-first substrate, 3-adhesive film for circuit connection, 4-second substrate, 5-conductive particles, 6-first adhesive layer, 7-second adhesive layer, 20-connection structure, 21-first circuit component, 22-first circuit substrate, 23-first electrode, 24-second circuit component, 25-second circuit substrate, 26-second electrode, 27-connecting portion, 30-remaining portion of the laminate.
Claims
1. A laminate comprising a first substrate, an adhesive film for circuit connection provided on the first substrate, and a second substrate provided on the adhesive film, wherein: When the adhesion strength of the first substrate to the adhesive film is represented by P1 and the adhesion strength of the second substrate to the adhesive film is represented by P2, P1 / P2 is 0.25 to 0.
80.
2. The laminate according to claim 1, wherein The adhesive film is a conductive adhesive film containing conductive particles.
3. The laminate according to claim 2, wherein: The adhesive film includes a first adhesive layer containing conductive particles and a second adhesive layer containing no conductive particles.
4. The laminate according to claim 3, wherein: The first substrate is adjacent to the first adhesive layer, and the second substrate is adjacent to the second adhesive layer.
5. The laminate according to any one of claims 1 to 4, wherein The adhesive film contains a heat-reactive component and a curing agent.
6. The laminate according to any one of claims 1 to 5, wherein The sealing strength P1 is 0.5 to 15 N / m, and the sealing strength P2 is 1.5 to 30 N / m.
7. The laminate according to any one of claims 1 to 6, wherein The first substrate is a substrate having a surface in contact with the adhesive film subjected to a release treatment.
8. A method for producing a laminate, the laminate comprising a first substrate, an adhesive film for circuit connection provided on the first substrate, and a second substrate provided on the adhesive film, wherein: The method for manufacturing the laminate comprises the following steps: The first substrate, the second substrate, and the adhesive film or a material for forming the adhesive film are prepared in such a manner that when the adhesion strength of the first substrate to the adhesive film is P1 and the adhesion strength of the second substrate to the adhesive film is P2, P1 / P2 is 0.25 to 0.80; and The laminate is obtained by arranging or forming the adhesive film between the first substrate and the second substrate.
9. A method for manufacturing a connection structure, the connection structure comprising a first circuit component having a first electrode, a second circuit component having a second electrode, and a connection portion disposed between the first circuit component and the second circuit component and electrically connecting the first electrode and the second electrode to each other, wherein: The method for manufacturing the connection structure comprises the following steps: The first substrate is removed from the laminate according to any one of claims 1 to 7, and the remaining portion of the laminate is disposed on the first circuit component in such a manner that the surface of the adhesive film in contact with the first substrate is in contact with the surface of the first circuit component on which the first electrode is provided; removing the second substrate from the remaining portion of the laminate, and disposing the second circuit component on the adhesive film in such a manner that the surface of the adhesive film in contact with the second substrate is in contact with the surface of the second circuit component provided with the second electrode; and The first circuit member and the second circuit member are thermally compressed to electrically connect the first electrode and the second electrode to each other.
